"(x^2+1)y''-2xy'+2y=6(x^2+1)^2"
Set "y=vx"
"\\implies y'=v+xv'" ,"y''=2v'+v''" .
Put this into the equation.
"(x^2+1)(2v'+xv'')-2x(v+xv')+2xv=6(x^2+1)^2\\\\\nx(x^2+1)v''+2x^2v'+2v'-2xv-2x^2v'+2xv=6(x^2+1)^2\\\\\nx(x^2+1)v''+2v'=6(x^2+1)^2\\\\"
Divide through by "x(x^2+1)" .
"v''+ \\frac{2}{x(x^2+1)}v'=\\frac{6(x^2+1)}{x}\\\\"
Set "u=v',u'=v''" .
"u'+ \\frac{2}{x(x^2+1)}u=\\frac{6(x^2+1)}{x}\\\\"
We will be needing an Integrating factor.
"I.F=e^{\\int\\frac{2}{x(x^2+1)}dx}=e^{\\int\\frac{2}{x}dx-{\\int\\frac{2}{x^2+1}dx}}\\\\\n=e^{2\\ln x-\\ln x^2+1}=\\frac{e^{\\ln x}}{e^{\\ln x^2+1}}=\\frac{x^2}{x^2+1}"
Multiply through by the "I.F"
"\\frac{x^2}{x^2+1}\\left(u'+ \\frac{2}{x(x^2+1)}u\\right)=\\frac{x^2}{x^2+1}\\left(\\frac{6(x^2+1)}{x}\\\\\\right)\\\\\n\\frac{d(u\\frac{x^2}{x^2+1})}{dx}=6x"
Integrate both sides
"u\\frac{x^2}{x^2+1}=\\int 6xdx\\\\\nu\\frac{x^2}{x^2+1}=3x^2+C\\\\\nu=3(x^2+1)+\\frac{C(x^2+1)}{x^2}\\\\\n\\text{But, } u=v'. \\text{So,}"
"v'=3(x^2+1)+\\frac{C(x^2+1)}{x^2}\\\\\n\\text{Integrate both sides}\\\\\nv=x^3+3x+\\frac{C(x^2-1)}{x}+K\\\\\n\\text{But, } v=\\frac{y}{x}. \\text{ So, }\\\\\ny=x^4+3x^2+C(x^2-1)+Kx\\\\\ny=x^4+(3+C)x^2+Kx-C"
Comments
Leave a comment